Nickel and Dimed : undercover in low-wage USA - Ehrenreich, Barbara 1941- (Granta Books, 2002)
Millions of Americans work full-time, year-round, for poverty level wages. Distinguished journalist Barbara Ehrenreich decided to join them, in order to find out how anyone survives on six to seven dollars an hour. Ehrenreich left home, took the cheapest lodgings she could find and accepted whatever job she was offered, from cleaning to care work, waitressing to folding clothes at Wal-Mart. So began a gruelling, hair-raising and darkly funny odyssey through the underside of working America.